Governance and Sustainable Development - Albassam, Bassam (The Arab Journal of Administration, 2021)
Providing public services efficiently and effectively and achieving the goals of strategic plans and visions requires a certain level of good governance. Therefore, governments seek to adopt principles of governance that are compatible with the economic and social components of the state. Thus, many governments face a challenge in determining the elements and procedures needed to good governing the public sector. This article states that population growth and the diversity of demands and needs of individuals, make it necessity for countries to strengthen local administration to meet these needs efficiently and effectively; and strengthening local governance requires applying good governance. This article analyzes and discusses the importance of governance in promoting economic and human development, the contribution of good governance to strengthening public participation in running the state’s affairs, and how to utilize e-government to reach advanced levels in good governance. This article concludes that sustainable and comprehensive development, especially in developing countries, requires adopting good governance in the public sector.